Quality Improvement of the Fishery Products from Songkla lake using Good Manufacturing Practices, Banchongfuen Fishing Community, Phatthalung Province, Thailand - Thanonkaew, Amonrat; Klompong, Vilailak; Pengnoo, Benjawan (Area Based Development Research Journal, 2024)
In Banchongfuen, Khomak sub Pakpayoon district, Phatthalung province, there were 24 fishery product producers who specialized in dried fishery products such as dried shrimp, dried ponyfish, dried spotted catfish, dusky-hairpin anchovy, and dried shortnose gizzard shad. However, these products did not meet certification standards for Good Manufacturing Practices (GMP) and Thai Food and Drug Administration (FDA). The Banchongfuen community group lacked the technology and facilities needed for fishery product processing at the community enterprise level. Their GMP scores were below 60% across all six aspects. The objective of this research was to improve the quality of fishery products to increase their value and establish community acceptance within the target community. The operation involved developing fishery product processing procedures to meet GMP standards, including locations and production buildings, production equipment and utensils, process control, sanitation, maintenance and cleaning, and personnel. The following step was applying for FDA certification for fishery products by requesting permission from the food production facility and obtaining an FDA number. As a result, products from Banchongfuen received certification of a food production location number (93-2-00465) from the Phatthalung Provincial Public Health Office. They proceeded to apply for FDA certification, and seven products successfully passed the certification process. These products included: 1) dried shrimp chili paste (93-2-00465-6-0001), 2) sun dried ponyfish (93-2-00465-6-0002), 3) dried shrimp with shell (93-2-00465-6-0003), 4) shrimp flavored rice seasoning (93-2-00465-6-0004), 5) sweet shrimp (93-2-00465-6-0005), 6) sun dried yellow shrimp (93-2-00465-6-0006) and 7) spotted catfish flavored rice seasoning (93-2-00465-6-0007). The income of the fishery product producers in Banchongfuen increased by 78.14% through selling fishery products, addressing issues for community-level entrepreneurs and adding value to fishery products.